Analisis Pengaruh Pembiayaan Musyarakah Terhadap Pendapatan Pembiayaan Bagi Hasil Pada Tiga Bank Umum Syariah Periode 2019 - 2021 - Putri Faraz Oktavi Yanti; Isro'iyatul Mubarokah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Islamic financial banking activities do not use the interest method, which is prohibited by Islamic law. Islamic banks can generate profit-sharing income from profit-sharing-based financing, one of which is musyarakah financing. Revenue sharing will increase in proportion to the level of public interest in musyarakah financing. Identifying the impact of musyarakah financing on revenue sharing simultaneously and significantly is the goal of this study. Associative quantitative methodology, which analyzes the link among two or more variables was used in this research. A sum of 36 variables, including samples of quarterly financial reports at three Indonesian Sharia conventional banks, specifically Bank Muamalat Indonesia, Bank Syariah Indonesia, and Bank BCA Syariah, were included in this research study. The data collection technique in this research is secondary data using samples of three quarterly financial report documents for Indonesian Sharia commercial banks on the OJK website for the period 2019 – 2021. An analysis of the classical assumption test, which includes the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test, as well as a simple linear regression assumption test, t test, and coefficient of determination test, was carried out to test this research using SPSS version 26. The conclusion of this research gives the result that Revenue sharing is significantly and favorably impacted by musyarakah finance with hypothesis H1 being accepted and hypothesis H0 being rejected